Vitamin B12 responsive developmental and epileptic encephalopathy due to a novel mutation in the FUT2 gene: a case report - PKBUC Bandara; Wasana Wijenayake; Sanjaya Fernando; Padmapani Padeniya; Sachith Mettananda (BMC, 2024)
Abstract Background Vitamin B12 deficiency is a recognised cause of neurological manifestations, including peripheral neuropathy, behavioural changes, and seizures. However, developmental and epileptic encephalopathy due to vitamin B12 deficiency is very rare. Here, we report an infant with vitamin B12-responsive developmental and epileptic encephalopathy due to a novel mutation in the fucosyltransferase 2 (FUT2) gene responsible for vitamin B12 absorption. Case presentation An 11-month-old girl of non-consanguineous parents presented with recurrent episodes of seizures since four months. Her seizures started as flexor epileptic spasms occurring in clusters resembling infantile epileptic spasms syndrome with hypsarrhythmia in the electroencephalogram. She was treated with multiple drugs, including high-dose prednisolone, vigabatrin, sodium valproate, levetiracetam and clobazam, without any response, and she continued to have seizures at 11 months. She had an early developmental delay with maximally achieving partial head control and responsive smile at four months. Her development regressed with the onset of seizure; at 11 months, her developmental age was below six weeks. On examination, she was pale and had generalised hypotonia with normal muscle power and reflexes. Her full blood count and blood picture revealed macrocytic anaemia with oval and round macrocytes. Bone marrow aspiration showed hypercellular marrow erythropoiesis with normoblastic and megaloblastic maturation. Due to the unusual association of refractory epilepsy and megaloblastic anaemia, a rare genetic disease of the vitamin B12 or folate pathways was suspected. The whole exome sequencing revealed a homozygous missense variant in exon 2 of the FUT2 gene associated with reduced vitamin B12 absorption and low plasma vitamin B12 levels, confirming the diagnosis of vitamin B12 deficiency related developmental and epileptic encephalopathy. She was started on intramuscular hydroxocobalamin, for which she showed a marked response with reduced seizure frequency. Conclusion We report a novel variant in the FUT2 gene associated with vitamin B12-responsive developmental and epileptic encephalopathy and megaloblastic anaemia. This case report highlights the importance of timely genetic testing in children with refractory developmental and epileptic encephalopathy to identify treatable causes.